Investigating the effects of Citrullus colocynthis pulp on oxidative stress in testes and epididymis in streptozotocin-induced diabetic male rats - Fereshteh Ostovan; Ali Gol; Abdolreza Javadi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Diabetes mellitus (DM) is one of the most common metabolic diseases in humans, affecting 100 million people around the world. Objective: Investigating the effects of Citrullus colocynthis pulp on oxidant and antioxidant factors of testes and epididymis in streptozotocin-induced diabetic male rats. Materials and Methods: Thirty-two male rats were divided into four groups eight each: 1) N (normal) group, 2) N+C group, 3) D (diabetic) group and 4) D+C group. Groups N and D received normal saline 2 ml orally for two weeks and groups N+C and D+C received 10 mg/kg.bw Citrullus colocynthis pulp orally for two weeks. Diabetes was induced by single intraperitoneal injection of streptozotocin (STZ) at 65 mg/kg. Results: D group had a significant increase in H2O2 (Hydrogen peroxide) and MDA (malondialdehyde) concentrations, and CAT (catalase) activity, and also a significant decrease in Peroxidase (POD) activity compared to N group. D+C group had a significant decrease in H2O2 and MDA concentrations and, CAT activity and significant increase in POD activity compared to D group. Conclusion: Citrullus colocynthis pulp in two weeks had beneficial effects on oxidants and antioxidants changes in reproductive system in streptozotocin-induced diabetic rats.